[PP.23.01] CULTURED TROPHOBLASTS ARE SALT-SENSITIVE WITH NA+ TRANSPORTERS DIFFERENTIALLY EXPRESSED IN PLACENTA OF PREGNANT RATS UPON PREGNANCY AND SALT EXPOSURE. (September 2017) - Scaife, P.; Mohaupt, M.; Klossner, R.; Eisele, N.; Kurlak, L.; Gennari-Moser, C.; Albrecht, C.; Pipkin, F. Broughton; Mistry, H.
Abstract : Objective: Previously, we and others have demonstrated that, in pregnancy, enhanced intake of NaCl lowers maternal blood pressure and improves pregnancy outcome for, as yet, unknown reasons. Non-renal targets, such as dendritic skin cells, respond to Na+ exposure thus as the dendritic cells are also present in the placenta, we hypothesised similar regulation to Na+ in trophoblasts upon Na+ challenge and thus can act as a novel salt sensor. Design and method: In vitro: Human choriocarcinoma cell line (BeWo), were incubated with a range of Na+ concentrations for 6 & 24 hours (110, 140 & 170 mM) in the absence or presence of forskolin (2x10–5 M), which forces syncytialization. In vivo: non-pregnant and pregnant rats were exposed to either normal, low (LS; NaCl 0.01%), high (HS; NaCl 8%) or high/low (HS/LS; 8% for first 14 days and then 0.01%) Na+ intake. All animals were sacrificed at day 20 and placentae were collected. TaqMan PCR was employed to examine the tonicity element binding protein (TonEBP); Na+ transporters: pendrin and ENaCs. Results: In vitro, TonEBP mRNA expression was elevated following NaCl incubation (p < 0.01- < 0.001). The ENaC α-subunit was down-regulated with higher Na+, whilst the γ-subunit was upregulated at both time points (p < 0.05-p < 0.001). The other ENaC subunits were expressed at very low levels. Pendrin was initially upregulated in BeWo cells at 6 hours, but not after 24 hours NaCl exposure (p < 0.01-p < 0.001). In comparison, exposure to HS and HS/LS diets enhanced placental pendrin (p < 0.05) in vivo. EnaCα and γ expression was increased in both the LS and HS/LS diet groups (p < 0.05). Conclusions: This study is the first to show that Na+ affects tonicity responses in trophoblast cells and placental tissue. Specific placental regulation of Na+ transporters suggests that the placenta may have a novel role as a Na+ sensor. These results implicate environmental factors, such as dietary salt, as having an important role in maintaining a successful pregnancy, although precise mechanisms have yet to be elucidated.